Analisis Kinerja Keuangan PT Indo Tambangraya Megah Tbk Tahun 2018-2022 - Sri Madona Saleh; Regina Cahyani (Jurnal Manajemen Bisnis Syariah, 2024)
The purpose of this study was to evaluate the financial performance before being affected by the covid-19 pandemic of PT Indo Tambangraya Megah Tbk in 2018-2022. The research method is quantitative research. The analysis technique uses liquidity, solvency, activity, and profitability ratio analysis. The data collection technique uses documentation in the form of financial statements of PT Indo Tambangraya Megah Tbk for 2018-2022 which are accessed through the official IDX / Indonesia Stock Exchange website. The results showed that the Liquidity Ratio of PT Indo Tambangraya Megah Tbk in 2018-2022 was in good condition or already above the industry average standard of similar companies. Judging from the Activity Ratio of PT Indo Tambangraya Megah Tbk in 2018-2022 is in good condition because each year is above good industry standards. Judging from the Profitability Ratio of PT. Indo Tambangraya Megah Tbk in 2018-2022 is in good condition. Judging from the solvency ratio of PT Indo Tambangraya Megah Tbk in 2018-2022 is in poor condition because the Company is below industry standards, it means that the Company is unable to optimize the assets owned by the Company which are financed by debt.